Simultaneous Purification and Separation of Syringoside and Oleuropein from Syringa oblata Lindl. Extract Using Macroporous Resin - Guoliang Li; Hongxiu Yan; Xiangping Liu (Journal of Chemistry)
This study developed an efficient method to simultaneously separate and purify syringoside and oleuropein from Syringa oblata Lindl. extract using macroporous resins. The adsorption and desorption property of 11 resins were systematically evaluated. Based on the adsorption performance, HPD-100B resin was selected for the separation of syringoside and oleuropein. The HPD-100B resin fitted well to the Langmuir isotherm model (R2 > 0.97), as ascertained by the results of the static adsorption experiment. Kinetic and dynamic adsorption/desorption experiments were conducted using the HPD-100B resin to optimize the separation parameters of syringoside and oleuropein. On the optimal parameters, syringoside and oleuropein were obtained from the 20% and 40% ethanol eluates, respectively. In addition, the adsorption effluent (15–60 BV) contained a large amount of syringoside with less impurities; therefore, this part was also collected for further syringoside separation and enrichment of syringoside. By only one cycle treatment, the syringoside and oleuropein contents in the final products increased by 7.1-fold and 8.2-fold, respectively, compared to the initial extract. The method developed in this study provides a potential basis for the industrial-scale enrichment and separation of syringoside and oleuropein from S. oblata extract.